A Stepwise Proposal for Low-Grade Hemorrhoidal Disease: Injection Sclerotherapy as a First-Line Treatment and Rubber Band Ligation for Persistent Relapses - Tutino, Roberta; Massani, Marco; Jospin Kamdem Mambou, Leonel; Venturelli, Paolina; Della Valle, Immacolata; Melfa, Giuseppina; Micheli, Matilde; Russo, Gaia; Scerrino, Gregorio; Bonventre, Sebastiano; Cocorullo, Gianfranco (Frontiers in Surgery, 2022)
Outpatient treatments are usually the techniques of choice in the management of low-grade hemorrhoidal disease; among these, rubber band ligation (RBL) and injection sclerotherapy (IS) are the most frequently performed. Both techniques are used, without one having been determined to be superior over the other. We analyzed the studies that compare these two techniques in terms of efficacy and safety in order to offer a proposal for treatment choice. RBL seems to be most efficient in terms of symptom resolution for second-degree hemorrhoidal disease and equal or superior for treatment of third-degree disease. However, IS offers lower rates of severe post-operative pain and minor complications. Since outpatient treatments are offered to patients as painless options that allow a prompt recovery, we propose a stepwise protocol using 3% polidocanol or aluminum potassium sulfate and tannic acid IS as the first treatment option, as it has less complications, followed by RBL in cases of relapse.